An encoderless high-performance synchronous reluctance motor drive - Hadla, Hazem (2020)
This paper presents an encoderless high-performance synchronous reluctance motor drive for traction applications. The control system is based on the active flux concept and a hybrid rotor position estimation algorithm is used, being this algorithm based on the injection of high-frequency signals at low speeds and on the position of the active flux vector for medium and high-speeds. A smooth transition algorithm between the two rotor position estimation methods is provided. Moreover, in order to improve the efficiency of the overall drive system, a loss minimization algorithm is proposed in order to reduce the motor copper losses when operating in steady-state. Experimental results obtained in the laboratory confirm the validity and adequacy of the proposed algorithms for the developed drive system.